Synergistic effect of co-combustion of EFB char with coal using bet analyzer - Naharudin, Nabilah (2019)
Renewable energy is becoming more popular worldwide due to economic crisis and critical source of conventional fossil fuel such as coal, petroleum, diesel and natural gas. Empty fruit bunch (EFB) char is one of the renewable energy sources that can replace coal and act as a fuel to generate steam and electricity. In this study, microwave pyrolysed EFB char was co-combusted with coal in order to achieve high efficiency for power generation from biomass/coal blends compared to the use of biomass standalone. The aim for this study was to identify the synergistic effect during cocombustion between EFB char with Mukah Balingian (MB) coal blends by using BrunauerEmmett-Teller (BET) analyser. The surface area of EFB char and MB coal blends were investigated over a range of different weight ratio and temperature. In this research, the weight ratio of EFB char/MB coal blends were from 100:0, 60:40, 20:80, and 0:100 and the temperature for co-combustion will be conducted at 400, 600, and 700°C.